2013
DOI: 10.1155/2013/650694
|View full text |Cite
|
Sign up to set email alerts
|

Skin Autofluorescence Relates to Soluble Receptor for Advanced Glycation End-Products and Albuminuria in Diabetes Mellitus

Abstract: The aim of this study was to compare skin autofluorescence caused by advanced glycation end-products (AGEs) with biochemical markers of endothelial dysfunction and soluble receptor for AGEs (sRAGE) in patients with diabetes. Skin autofluorescence (AF) assessed by AGE-Reader was evaluated with sRAGE and other biochemical parameters in 88 patients with diabetes (47 Type 1/T1DM/ and 41 Type 2/T2DM/) and 20 controls. Skin AF was significantly higher in T1DM and T2DM in comparison to controls (2.39 ± 0.54, 2.63 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…As expected, in our diabetics, the age-dependent rise of SAF was much steeper than in the nondiabetic controls. These data correspond well with studies from Netherlands [ 67 , 68 ] and from the Czech Republic [ 69 ]. In contrast, a large Australian study reported only a tendency towards higher SAF values [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…As expected, in our diabetics, the age-dependent rise of SAF was much steeper than in the nondiabetic controls. These data correspond well with studies from Netherlands [ 67 , 68 ] and from the Czech Republic [ 69 ]. In contrast, a large Australian study reported only a tendency towards higher SAF values [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…For example, the AGE-related fluorescence of skin and the eye lens have been measured [132][133][134][135][136]. Interestingly, AGE-related fluorescence of the human skin has been correlated with vascular complications [137], renal function [132,138,139], diabetes [140], obesity [141], and even mental disorders [142].…”
Section: Fluorescence Spectrometrymentioning
confidence: 99%
“…12 Skrha and colleagues measured SAF in subjects with type 1 or type 2 diabetes vs. control subjects and reported that in the diabetic groups, SAF levels were higher vs. controls and correlated positively with levels of sRAGE. 13 Significantly higher SAF also correlated with indices of endothelial dysfunction such as levels of von Willebrand factor, Intercellular Adhesion Molecule 1 (ICAM1), and Vascular Cell Adhesion Molecule 1 (VCAM1) in that study. Levels of sRAGEs were not measured in the present study by de Vos and colleagues but others measured sRAGE in human subjects with coronary artery disease and PAD and found lower levels of sRAGE in subjects with both sites of disease.…”
mentioning
confidence: 50%